Dietary quality and adherence to dietary recommendations in Chinese patients with chronic kidney disease - Ouyang, Wenwei; Xiao, Bingjie; Chen, Huifen; Fu, Lizhe; Tang, Fang; Marrone, Gaetano; Liu, Xusheng; Wu, Yifan; Carrero, Juan Jesús (Frontiers in Nutrition, 2025)
ObjectivesThere is a lack of data regarding the quality of the diet and the adherence to dietary guidelines of patients with non-dialysis-dependent CKD (NDD-CKD) in China.Design and methodsSingle-center cross-sectional study of 261 patients with CKD stages 3–5, who responded to 3-day dietary records and undertook 24-h urine samples along with clinical, laboratory, and anthropometric assessments. We compared their food intake with Chinese recommendations for CKD patients, assessed dietary quality through the Chinese Healthy Eating Index (CHEI), and calculated the contribution to energy intake by processed foods according to the NOVA classification.ResultsAverage energy intake was 30 ± 9 Kcal/kg/d, and 65% consumed less energy than recommended. The average protein intake was 1.2 ± 0.5 g/Kg/d, and 81% consumed more than recommended. 71% of patients consumed excess sodium and 80% consumed too little fiber. These proportions worsened across more severe CKD stages (all P trend value <0.05). The diet was considered of moderate quality (CHEI score 59.5 ± 11.0), and patients with CKD stages 4–5 scored progressively worse (P trend = 0.008). Total grains and tubers supplied 50 and 30% of the total energy and protein intake, respectively. Processed and ultra-processed foods contributed to 23.3% of dietary energy and 11.7% of food weight.ConclusionA large proportion of NDD-CKD at our center showed low adherence to diet recommendations. Although consumption of processed foods was low, diet quality worsened with more severe CKD, with low intake of whole grains, dairy, and soybean.